Pedagogical leadership and professional performance of teachers in Educational Institution No. 32211 José Carlos Mariátegui “El Amauta”, Ugel N° 05 Yarowilca 2019 - Godoy-Tucto, Yudi (2021)
The purpose of the study was to prove that there is a high correlation between pedagogical leadership and professional teaching performance in the Educational Institution No. 32211 José Carlos Mariátegui “El Amauta”, jurisdiction of the UGEL 05 of Yarowilca during the academic year 2019; for this, a correlational research and non-experimental design was formulated, a sample population of 10 teachers was worked on, including the director of the educational institution; The data collection instrument used was a valued test, including five dimensions and for each one, four indicators with grades from 1 to 5, which produced the scale of [4 - 20], for the five dimensions studied in the variable one; for the data processing, the simple linear regression and correlation was used, obtaining the following result and conclusion: there is a very high and positive correlation, so the degree of dependence is 97.89%, between pedagogical leadership and professional performance of teachers at the Educational Institution No. 32211, José Carlos Mariátegui “El Amauta” of Yarowilca.